(untitled) (Texas Journal of Medical Science, 2023)
Atrioventricular nodular reciprocal tachycardia is determined by the presence of a rientry mechanism in the zone of the AV node. The AV node has a three-dimensional structure and weak connections in the slot contacts due to the differentiated expression of connexin isoforms. These conditions cause the formation of nodal reciprocal tachycardia [1,2,3].There is also histological and electrophysiological evidence that the lower right and left extensions of the human AV node and the atrioventricular messages they provide can become an anatomical substrate for slow AV conduction[4].Ablation of AV nodular reciprocal tachycardia ranks second in frequency among all catheter interventions[5].ANRT is more common in women than in men